Maize progenitor selection to obtain hybrid seeds by small farmers. - Valdivia, Roberto (2006)
The seed of actual high yielding hybrids are very expensive and local farmers tend to use advanced generations to reduce costs. Abetter choice is to produce seed of maize intervarietal hybrids. The objective of this research was to describe the experience of a group of maize producers in the seed production, utilization and improvement of their parents of intervarietal hybrids. The study was conducted in Nayarit State, Mexico. In 1996, a group farmers, supported by a technical researcher, evaluated two maize intervarietal crosses. The cross B840xC343 yielded better than nine commercial hybrids. This motived the farmers to produce 20 tons of seed in eight intervarietal crosses during the winter season of 1997/98. The cost of the seed production was 50% less than the cost of commercial hybrid seed. The eight intervarietal crosses were commercial planted in about 400 hectars and were evaluated in four experiments by the farmers. The results showed that two crosses, P3028xA7573 and C385xD880, had the best results. The first cross had a heterosis of 4.1% over the high yielding parent and the second a heterosis of 30% over a parent. Since 1999, the parents of the best intervarietal cross is being improved by reciprocal recurrent selection of half siblings, two years per cycle.